Detection Fraudulent Financial Reporting Using the Fraud Hexagon Model with Corporate Governance Mechanisms as Moderator - Afida Defi Maulida; Imang Dapit Pamungkas (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study discusses the influence of six fraud hexagon models: pressure, opportunity, rationalization, capability, arrogance, and collusion on fraudulent financial reporting (FFR) practices in the Indonesia banking sector. In addition, this study analyzes the role of corporate governance mechanisms measured by the audit committee, managerial ownership, and institutional ownership as moderating variables. The sample consists of 43 banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period, with a total of 172 observations. Data analysis was conducted using WarpPLS 8.0. The results indicate that rationalization, capability, and arrogance have a significant positive effect on FFR, while pressure, opportunity, and collusion show no significant effect. The audit committee, managerial ownership, and institutional ownership also do not have a direct effect on FFR. However, these three variables act as moderators: the audit committee moderates the relationship between collusion on FFR, managerial ownership moderates the relationship between capability on FFR, while institutional ownership moderates the relationship between pressure and opportunity on FFR. This finding emphasizes the importance of effective corporate governance as an instrument to reduce the risk of FFR in the banking sector.